Investigation on g-C3N4/rGO/TiO2 nanocomposite with enhanced photocatalytic degradation performance. (September 2021) - Hu, Faguan; Sun, Shiping; Xu, Hongliang; Li, Mingliang; Hao, Xiaofei; Shao, Gang; Wang, Hailong; Chen, Deliang; Lu, Hongxia; Zhang, Rui
Abstract: Three phase nanocomposites g-C3 N4 /rGO/TiO2 were synthesized successfully under hydrothermal reaction conditions using g-C3 N4 nanosheets as matrix, as well as TiO2 sol and graphene oxide as the precursors of nano-size anatase and reduced graphene oxide (rGO), respectively. The photocatalytic performance of samples was investigated by degrading Rhodamine B (RhB) solution under sunlight irradiation with a xenon lamp. The results show that g-C3 N4 /rGO/TiO2 three-phase composite nanomaterial was successfully prepared. g-C3 N4 /rGO/TiO2 exhibited a satisfactory photocatalytic activity and cycle stability when the mass ratio of g-C3 N4 nanosheets (0.6 g) to nano-TiO2 (0.2 g) was 3:1, the mass of GO was 0.002 g, the hydrothermal temperature and time were 160 °C and 6 h, respectively. When photocatalysis for 60 min, the degradation rate of RhB solution (100 mL, 10 mg/L) by g-C3 N4 /rGO/TiO2 (100 mg) reached 99.63%. Main reasons for these results lie in the significantly improved separation efficiency of photogenerated electron-hole pairs due to the construction of g-C3 N4 /TiO2 heterojunction, the enhanced optical absorption and the increased specific surface area. Graphical abstract: Image 1 Highlights: g-C3 N4 /rGO/TiO2 nanocomposite was prepared by a facile process. The g-C3 N4 nanosheets were below 10 nm and the diameter of nano-TiO2 was about 10 nm. g-C3 N4 /rGO/TiO2 nanocomposite exhibited excellent photocatalytic activity and degraded RhB within 50 min under visible light. Rate constant value of g-C3 N4 /rGO/TiO2 is 8.99 times higher than that of common g-C3 N4 .